"On‐Water" Palladium‐Catalyzed Tandem Cyclization Reaction for the Synthesis of Biologically Relevant 4‐Arylquinazolines. Issue 57 (18th September 2019) - Yuan, Shuo; Yu, Bin; Liu, Hong‐Min
Abstract: The quinazoline scaffold is prevalent in pharmaceutically relevant molecules that show diverse biological activities. Herein, we report an efficient "on‐water" palladium‐catalyzed tandem cyclization reaction from commercially available arylboronic acids and benzonitriles that enable the rapid access to 4‐arylquinazoline scaffolds in good to excellent yields (45 examples, up to 98 % yield). This protocol has shown good functional group tolerance and broad substrate scope. The reaction was also performed on a gram scale and successfully applied to the synthesis of the highly potent and selective PI3Kδ inhibitor N11, showing the practicability and synthetic utility of the protocol. In this reaction, the quinazoline scaffold is efficiently constructed with the simultaneous formation of one C−C bond and one C−N bond. Collectively, the protocol could serve as an alternative strategy to synthesize biologically important quinazoline scaffolds. Abstract : Better "on water" : An efficient palladium‐catalyzed tandem cyclization reaction from readily available arylboronic acids and benzonitriles on water has been developed to offer a rapid access to the quinazoline scaffolds in good to excellent yields (up to 98 % yield). This protocol is also performed on a gram scale and successfully applied to the synthesis of the highly potent and selective PI3Kδ inhibitor N11.